Physical recovery of post-exercice footballers of both sexes through the glycemic index. [A field study on the teams of ESF Farfar males and Meshal Zayban female in Biskra, Algeria.] - merabet djemali (sports creativity, 2025)
The aim of this study is to highlight whether there is a difference in the glycemic index or not between the sexes of football players during the recovery period following physical performance (exercise), For this, we selected a sample of 16 individuals (08 males and 08 females) by intent. We subjected the sample to the same physical effort (high intensity and another low intensity), from the above, the researcher's intervention in the phenomenon is clear, so the approach is the experimental approach. After analyzing the results obtained based on SPSS program and discussing it, we reached the following conclusions: There are statistically significant differences in the glycemic index at rest between males and females of the research sample and in favor of females, There are no statistically significant differences in the glycemic index after high intensity exercise between males and females of the research sample, There are statistically significant differences in the glycemic index after low intensity exercise between males and females of the research sample and in favor of males